Atezolizumab and pembrolizumab in triple-negative breast cancer: a meta-analysis. Issue 2 (1st February 2022) - Latif, Farah; Bint Abdul Jabbar, Hira; Malik, Hamna; Sadaf, Humaira; Sarfraz, Azza; Sarfraz, Zouina; Cherrez-Ojeda, Ivan
ABSTRACT: Background: The approval of anti-PD-L1 drugs, including atezolizumab/pembrolizumab in triple-negative breast cancer (TNBC), potentially improveme treatment regimens available for TNBC. Methods: We conducted a meta-analysis to review the efficacy of atezolizumab/pembrolizumab for the treatment of TNBC in both the adjuvant and neoadjuvant settings. We calculated standardized mean difference (SMD) for the associations of progression-free survival (PFS) and overall survival (OS) and odds ratios (ORs) to estimate objective response rate (ORR) and pathological complete response (pCR), using 95% confidence intervals (CIs). Results: Six clinical trials comprising 3612 patients were included. For adjuvant therapies, the ORR (OR = 1.26, P = 0.04) of atezolizumab/pembrolizumab plus chemotherapy was higher in the intention to treat (ITT) arms than the placebo groups in TNBC. A positive effect size was found for PFS in the ITT arms (d = 1.55, P < 0.001). The atezolizumab plus chemotherapy group had a positive effect size for OS compared to control groups (d = 0.52, P < 0.001). In the neoadjuvant setting, patients in ITT arms had higher pCR rates than the control groups (OR = 1.61, P = 0.001). Conclusion: We collate evidence of atezolizumab/pembrolizumab as viable therapeutics among patients with TNBC with PD-L1 subgroups deriving higher benefits. PLAIN LANGUAGE SUMMARY: Immune checkpoint inhibitors (ICI), atezolizumab and pembrolizumab, have received approval for patients with triple-negative breast cancer (TNBC) expressing PD-L1. Thus far, it has only been approved for patients with unresectable locally advanced or metastatic TNBC. With the IMpassion 130 and KEYNOTE-355 trials introducing the immunotherapy era for TNBC, ongoing trials have started exploring the outcomes of the ICIs in early-stage TNBC in combination. Recently, the ICIs have demonstrated positive efficacy outcomes in neoadjuvant settings. Both the ICIs have shown a safe profile in terms of adverse events. The recent advances made by clinical trials indicate promising results for early-stage and advanced/metastatic TNBC. However, there is a need to harmonize and explore biomarkers and endpoints in the ongoing clinical trials to enhance patient treatment protocols. As TNBC is an aggressive subtype, exploring beyond the PD-L1 positive subgroup is necessary to expand the target population receiving ICIs for TNBC.